2014
DOI: 10.1038/labinvest.2014.97
|View full text |Cite
|
Sign up to set email alerts
|

Activin A balance regulates epithelial invasiveness and tumorigenesis

Abstract: Activin A is a member of the TGFβ superfamily. Activin A and TGFβ have multiple common downstream targets and have been described to merge in their intracellular signaling cascades and function. We have previously demonstrated that coordinated loss of E-cadherin and TGFβ receptor II results in epithelial cell invasion. When grown in three-dimensional organotypic reconstruct cultures, esophageal keratinocytes expressing dominant-negative mutants of E-cadherin and TGFβ receptor II showed activated Smad2 in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…Activin A is also associated with the maintenance of neuron survival, induction of hepatocyte apoptosis, promotion of erythroid differentiation and dual regulation of macrophage activation (14)(15)(16)(17). The involvement of activin A in the process of tumor genesis and progression has been previously reported (18), and a significant increase of activin A in the serum of certain patients with colorectal adenocarcinoma has been observed (19). However, the function of activin A in tumor progression is controversial.…”
Section: Discussionmentioning
confidence: 92%
“…Activin A is also associated with the maintenance of neuron survival, induction of hepatocyte apoptosis, promotion of erythroid differentiation and dual regulation of macrophage activation (14)(15)(16)(17). The involvement of activin A in the process of tumor genesis and progression has been previously reported (18), and a significant increase of activin A in the serum of certain patients with colorectal adenocarcinoma has been observed (19). However, the function of activin A in tumor progression is controversial.…”
Section: Discussionmentioning
confidence: 92%
“…We have previously shown the ability of nAb and A83-01 to neutralize Activin A signaling in this model system [34, 48]. Treatment with nAb increased cell invasion in dysplastic empty vector control cells, yet could not overcome the inhibition of cell invasion in the context of Fibro-ActA cultures (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Considering elevated levels of Activin A are found in the stroma despite the characteristic function of Activin A as an inducer of growth arrest, we first aimed to investigate the role of microenvironment-derived Activin A in a three-dimensional organotypic reconstruct (OTC) model in the presence of dysplastic esophageal keratinocytes (ECdnT) [29]. As normal esophageal fibroblasts secrete low to negligible levels of Activin A ([34] and data not shown), we retroviral transduced fibroblasts with INHBA to achieve Activin A overexpression levels similar to those observed in cancer-associated fibroblasts [34, 43]. Upon embedding Activin A overexpressing fibroblasts (Fibro-ActA) in the organotypic culture matrix, we validated overexpression and secretion of Activin A by ELISA (Additional file 2: Figure S2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ActA levels were reported to be increased in patients with breast cancer (40) and in some mouse tumor models (41), new data showed that ActA protein in lung adenocarcinoma tissue was significantly lower than in normal lung tissue (42) and ActA may inhibit proliferation of breast cancer cell lines (43,44). It is likely that ActA can activate autocrine and paracrine signaling affecting crosstalk between the epithelial compartment and the surrounding microenvironment (45) in a cell-type and context-dependent manner supporting or inhibiting tumor development (38). Without better understanding the controversial role of ActA in cancer, the use of ActA as a systemic pharmacological agent appears not suitable (39).…”
Section: Discussionmentioning
confidence: 99%